2016
DOI: 10.1186/s12933-016-0392-7
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of diabetes, hypertension and obesity among immigrants from East Africa and the former Soviet Union: a retrospective comparative 30-year cohort study

Abstract: BackgroundPrevious studies have reported an increasing prevalence of metabolic abnormalities in immigrants who moved from low-cardiovascular-risk regions to Western countries, but little is known about time trends following immigration.MethodsA retrospective cohort study of immigrants from Ethiopia in east Africa (EAI), the former Soviet Union (FSUI) and native-born Israelis (NBI) over a 35-year period. EAI were divided into three groups by date of immigration. Associations between ethnicity, age, sex and meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 37 publications
1
32
0
1
Order By: Relevance
“…In fact, Ethiopian women with GDM had significantly lower body weight compared to reference and Arab women with GDM. The higher risk of GDM among Ethiopian women is in line with recent studies showing high risk of adult-onset DM among Ethiopian Jews younger than 50 years of age, particularly women [15,16,19]. In our study, Arab ethnicity was not found to be significantly associated with a greater risk of GDM, although Arab women had higher prevalence of pre-gestational diabetes compared to non-Ethiopian Jewish women.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In fact, Ethiopian women with GDM had significantly lower body weight compared to reference and Arab women with GDM. The higher risk of GDM among Ethiopian women is in line with recent studies showing high risk of adult-onset DM among Ethiopian Jews younger than 50 years of age, particularly women [15,16,19]. In our study, Arab ethnicity was not found to be significantly associated with a greater risk of GDM, although Arab women had higher prevalence of pre-gestational diabetes compared to non-Ethiopian Jewish women.…”
Section: Discussionsupporting
confidence: 90%
“…On arrival to Israel, the prevalence of DM among Ethiopian Jews was less than 1% [14] and increased rapidly thereafter. Recent studies reported higher prevalence of DM among Ethiopian Jewish women at reproductive age and lower prevalence of obesity compared to the majority group of non-Ethiopian Jewish women in Israel [15,16].…”
mentioning
confidence: 97%
“…Indeed, favorable trends in the prevalence of hypertension, dyslipidemia, and cigarette smoking have been observed in Western countries [18, 19]. However, the evidence from Western populations cannot simply be extrapolated to Asian populations because there are ethnic differences in both the prevalence of cardiovascular risk factors and their association with diabetes [31]. …”
Section: Discussionmentioning
confidence: 99%
“…The low prevalence rates of fasting hyperglycemia are also related to a low prevalence of 2 other traditional hepatic risk markers for diabetes (fasting hypertriglyceridemia and increased hepatic fat content) across Black populations around the world (14)(15)(16)(17)(18)(19)(20). The presence of these 3 risk factors predicts a faster decline in glucose tolerance, especially among individuals of European ancestry (21).…”
Section: Introductionmentioning
confidence: 99%